Impact of cavity shave margins in patients with ductal carcinoma in situ undergoing conserving breast surgery - Vanni, Gianluca; Pellicciaro, Marco; Materazzo, Marco; Marsella, Valentina; Usai, Valeria; Noce, Annalisa; Buonomo, Oreste Claudio (Frontiers in Oncology, 2024)
The main challenge during breast-conserving surgery (BCS) is to obtain clear margins especially in patients with ductal carcinoma in situ (DCIS) due to the absence of well-defined nodule. Many surgical approaches have been used with the attempt to reduce the positive margins rate. The aim of this retrospective study is to compare cavity shave margin technique with standard surgery and intraoperative evaluation of surgical margins. Methods: A single center retrospective study analyzing margins status, re-excision and surgical time on a cohort of 227 patients from September 2016 to September 2022. Results: In patients subjected to cavity shave we reported a significative reduction of positive margins 17.1% vs 28.7% (p-value=0.042). Also, a difference in term of surgical re-excision was reported p-value=0.039 (12.4% vs 23.8% respectively for cavity shave and control group). At the multivariate analysis, intra-operative evaluation of the margins was a risk factor for margins re-excision (Wald 4.315, p = 0.038, OR: 2.331, 95%CI: 1.049-5.180). Surgical time was lower in patients subjected to cavity shave p=0.024 and relative mean time was 68.4±37.1 in the cavity shave group versus 93.9±40.6 minutes in the control group.Cavity shave margin technique in conserving breast surgery results in a reduction in positive margin rate, surgical re-excision and operative time.